2020
DOI: 10.2174/1874467213666200102095023
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lacosamide in Preventing Pentylenetetrazole Kindling-Induced Alterations in the Expression of the Gamma-2 Subunit of the GABAA Receptor in Rats

Abstract: Background: Epilepsy remains challenging to treat still no etiologic treatment has been identified, however, some antiepileptic drugs (AEDs) are able to modify the pathogenesis of the disease. Lacosamide (LCM) has been shown to possess complex anticonvulsant and neuroprotective actions, being an enhancer of the slow inactivation of voltage-gated sodium channels, and it has the potential to prevent epileptogenesis. Recent evidence has shown that LCM indirectly improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Our results regarding lacosamide are in agreement with previous researchers who have found that the drug is effective in the suppression of amygdala kindling at doses 10 and 30 mg/kg while the lowest dose of 3 mg/kg was ineffective (Brandt et al 2006). In addition, there is data that lacosamide reduces the maximal intensity of PTZ-induced seizures and produces modulatory effects on the GABAergyc system (Gáll et al 2020). The results from the current study complete our previous result where we found that lacosamide at a dose of 30 mg/kg has a pronounced antiepileptogenic effect in a model of temporal lobe epilepsy induced by a single injection of pilocarpine (Shishmanova-Doseva et al 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Our results regarding lacosamide are in agreement with previous researchers who have found that the drug is effective in the suppression of amygdala kindling at doses 10 and 30 mg/kg while the lowest dose of 3 mg/kg was ineffective (Brandt et al 2006). In addition, there is data that lacosamide reduces the maximal intensity of PTZ-induced seizures and produces modulatory effects on the GABAergyc system (Gáll et al 2020). The results from the current study complete our previous result where we found that lacosamide at a dose of 30 mg/kg has a pronounced antiepileptogenic effect in a model of temporal lobe epilepsy induced by a single injection of pilocarpine (Shishmanova-Doseva et al 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Similar behavior was observed by Gáll et al [34] in which treatment with LCM (10 mg/kg, intraperitoneally) daily for 57 days reduced the maximum intensity of the seizures induced by PTZ, but was unable to prevent kindling. Interestingly, chronic administration of a new hybrid compound (designated C11) synthesized from the drugs lacosamide, ethosuximide (ETS), and levetiracetam (LEV) suppressed the progression of seizures in the model induced by repeated administrations of PTZ in mice [35].…”
Section: Discussionsupporting
confidence: 87%
“…Despite lacking spontaneous seizures, a seizure threshold decrease in kindled animals mimics epilepsy phenotypes through an imbalance between the excitatory and inhibitory neurotransmission systems. [ 31 , 32 , 33 ]. In addition, the PTZ-kindling model has been shown to reflect the cognitive impairments [ 34 , 35 ] and the characteristic cellular changes related to epilepsy in rats, such as astrogliosis [ 18 ] and microglia activation [ 36 ].…”
Section: Introductionmentioning
confidence: 99%